Bank Credit, Asset Prices and Financial Stability : Evidence From French Banks - Pouvelle, Cyril (IMF Working Papers; Working Paper, 2012)
This paper analyses the effect of asset prices on credit growth in France and tries to disentangle credit demand and supply factors, both for the whole 1993-2010 period and during periods of financial instability. Using bank-level panel data at a quarterly frequency, stock price growth is shown to have a significant effect on lending growth over the whole period, but without credit supply factors being singled out. By contrast, housing price growth has a significant effect during periods of financial instability only, even after controlling for credit demand effects. These results show that credit demand factors do play a large role but also provide evidence of tighter credit constraints on households in financial instability periods.